The Effectiveness of Chemistry Tricky Test Game in Online Learning when Covid-19 Pandemic - Devita Diah Aprilia; achmad lutfi (Universitas Negeri Surabaya, 2023)
This stydy is purposed to determine the effectiveness of learning chemistry on Hydrocarbon chapter by using the Tricky Test Game when Covid-19 appear based on completeness of learning outcomes. The research is a quantitative research. The research method used pre-experimental using one group pretest and posttest design. The sample in this study was 25 students of class XII in Bojonegoro Integrated High School as an experimental class chosen by cluster random sampling. The instrument used is a multiple choice test to do the pretest and posttest also response questionnaire. The results obtained that Chemistry Tricky Test is responded very well by students as an appropriate media game for learning chemistry daring on hydrocarbon material, there is a significant difference between the results of the pretest and posttest results and Classical completeness after using Chemistry Tricky Test reaches 100%. Then it can be concluded that the use of tricky test games can effectively improve the learning completeness in Bojonegoro Integrated High School.